Dykes on Mykes: Podcasting and the Activist Archive - Hogan, Mel (TOPIA: Canadian Journal of Cultural Studies, 2008)

The Importance of Community-Based Media for Building and Sustaining Lesbian Subcultures: The Role of Montréal’s Dykes on Mykes Radio Show - MacPhee, Marie-Claire; Hogan, Mél (Global Media Journal, 2006)
This paper was originally written for and presented at the Lesbian Lives XIII: Historicizing the Lesbian Conference in Dublin, Ireland in February 2006. The essay considers the history of Dykes on Mykes, a groundbreaking, lesbian and queer community-based radio program in Montréal, Canada. The authors, who are the show’s current hosts and technicians, collected data by examining the show’s archives and conducting individual and focus group interviews with Dykes on Mykes’ past and present hosts. These data reveal that changes in Dykes on Mykes’ programming and foci correlate closely with contemporary cultural and social developments among lesbian communities in Montréal.

The Role of Montréal’s Dykes on Mykes Radio Show - MacPhee, Marie-Claire; Hogan, Mél (Canadian Woman Studies, 2006)
Les auteures examinent le rôle historique, socio-politique de la programmation radiophonique montréalaise des années ‘20 alors que Dykes on Mykes, une émission qui a forgé et soutenu la sous-culture des lesbiennes et queers de la communauté anglophone de Montréal. Elles assurent que l’émission Dykes on Mykes a initié un courant alternatif à l’ordre établi en travaillant directement avec la communauté lesbienne et queer de Montréal et en contribuant à leur représentation positive dans les médias.